2008
DOI: 10.1016/j.ajog.2008.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Nucleated red blood cells are a direct response to mediators of inflammation in newborns with early-onset neonatal sepsis

Abstract: Objective-To test the hypothesis that inflammation modulates fetal erythroblastosis and/or the release of NRBCs independent of hypoxia or fetal stress. We sought to determine if fetal inflammation is associated with an elevation in neonatal NRBC count in the setting of inflammation-associated preterm birth.Study Design-The relationships between peripheral NRBC count, histological chorioamnionitis, umbilical cord interleukin-6 (IL-6), erythropoietin (EPO), cortisol and acid-base status were analyzed in 68 prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 40 publications
(54 reference statements)
3
38
2
Order By: Relevance
“…This finding is consistent with our previous study in humans, which demonstrated that inflammation represents an important stimulus for nucleated red blood cell production or release in the absence of hypoxia. 86 Thus, from our previously published data, coupled with the results presented here, we conclude that the process of fetal inflammation comprises a variety of acute and chronic pathological processes that collectively induce an imbalance in tissue homeostasis characterized by extracellular release of DAMPs and tissue damage. The current study puts forth the hypothesis that RAGE and HMGB1 are active participants in mediating the process of fetal and neonatal tissue injury that may lead to multiple organ dysfunction.…”
Section: Damps and Fetal Inflammation 971supporting
confidence: 80%
“…This finding is consistent with our previous study in humans, which demonstrated that inflammation represents an important stimulus for nucleated red blood cell production or release in the absence of hypoxia. 86 Thus, from our previously published data, coupled with the results presented here, we conclude that the process of fetal inflammation comprises a variety of acute and chronic pathological processes that collectively induce an imbalance in tissue homeostasis characterized by extracellular release of DAMPs and tissue damage. The current study puts forth the hypothesis that RAGE and HMGB1 are active participants in mediating the process of fetal and neonatal tissue injury that may lead to multiple organ dysfunction.…”
Section: Damps and Fetal Inflammation 971supporting
confidence: 80%
“…For obvious reasons, it would be impossible to control a human study to such an extent. This type of model allows us to eliminate the potential influence of other factors that may affect the NRBC count in the human, such as prematurity or infection/inflammation 33,43…”
Section: Discussionmentioning
confidence: 99%
“…In fetuses, Dulay et al [29] demonstrated the increase in the number of nRBCs in preterm neonates with evidence of choriamnionitis and in the absence of hypoxia. These authors [30] assessed nRBCs counts within 1 h of birth in 68 preterm singletons, establishing a significant correlation between nRBC count and cord blood interleukin-6 level.…”
Section: Discussionmentioning
confidence: 99%